People’s transformation through community library: a brief study of READ philosophy - Pokhrel, Murari Binod (Access: An International Journal of Nepal Library Association, 2022)
The article aims to briefly highlight how, where and what situation led to the establishment of Rural Education And Development (READ) in Nepal. It also slightly explains how the request 'if you can establish a community library in my village' told by a common person has touched the inner heart of the person, who has educational research background herself. The article states about READ model a bit: Community involvement from planning, infrastructure management, rules and regulations formation, develop sustainable projects for daily management of the library. It states that the library is for the community, by the community, within the community. READ model has a vision, mission and strategy, so as all READ supported libraries. So far all READ supported libraries are managed on their own. It is because, all political parties, community people from children to elderly ones', local authority and all stakeholders within the community feels 'it is ours'. Thus, it seems that the future of READ libraries are driven in the right direction.